L-band mobile satellite signal performance using handheld gps receiver - Thian,, Kee Fong (Universiti Malaysia Sarawak, UNIMAS, 2009)
This project presents a method to analyse the signal performance from the L-Band Mobile Satellite (MS) by using the handheld Global Positioning System (GPS) receiver. In this project, a simple and low-cost data acquisition system that can be used to carry out measurement for different mobile satellite environments is proposed.